A major checkpoint for protein expression in Rhodobacter sphaeroides during heat stress response occurs at the level of translation. (19th October 2021) - McIntosh, Matthew; Köchling, Thorsten; Latz, Anna; Kretz, Jonas; Heinen, Sandra; Konzer, Anne; Klug, Gabriele
Summary: Temperature above the physiological optimum is a stress condition frequently faced by bacteria in their natural environments. Here, we were interested in the correlation between levels of RNA and protein under heat stress. Changes in RNA and protein levels were documented in cultures of Rhodobacter sphaeroides using RNA sequencing, quantitative mass spectrometry, western blot analysis, in vivo [ 35 S] methionine‐labelling and plasmid‐borne reporter fusions. Changes in the transcriptome were extensive. Strikingly, the proteome remained unchanged except for very few proteins. Examples include a heat shock protein, a DUF1127 protein of unknown function and sigma factor proteins from leaderless transcripts. Insight from this study indicates that R. sphaeroides responds to heat stress by producing a broad range of transcripts while simultaneously preventing translation from nearly all of them, and that this selective production of protein depends on the untranslated region of the transcript. We conclude that measurements of transcript abundance are insufficient to understand gene regulation. Rather, translation can be an important checkpoint for protein expression under certain environmental conditions. Furthermore, during heat shock, regulation at the level of transcription might represent preparation for survival in an unpredictable environment while regulation at translation ensures production of only a few proteins.